2018
DOI: 10.1097/qai.0000000000001609
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Serological Tests Ineffectively Screen for HIV Exposure in HIV-Positive Infants

Abstract: These data suggest that the use of rapid serological tests may have inadequate performance as an indicator of exposure and potential HIV infection among infants presenting at both well-child (immunization and community outreach) and sick-infant (nutrition and inpatient) entry points. To improve the identification of HIV-positive infants, nucleic acid-based testing should instead be considered in infants aged younger than 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The absence of HIV molecular diagnosis in the clinical routine in EG does not allow the early diagnosis of HIV-exposed children born to HIV-infected women, which is essential to prevent the rapid progression of the disease in a country with a high (25%) mother-to-child HIV transmission rate [ 51 ]. The only diagnostic option available for children < 18 months is repeated rapid serological testing, which increases the risk of false HIV diagnoses and infant mortality if not treated in time [ 52 ]. The 2 (8%, 2/25) HIV-exposed children who were infected died before they could receive a confirmatory diagnosis and adequate ART.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of HIV molecular diagnosis in the clinical routine in EG does not allow the early diagnosis of HIV-exposed children born to HIV-infected women, which is essential to prevent the rapid progression of the disease in a country with a high (25%) mother-to-child HIV transmission rate [ 51 ]. The only diagnostic option available for children < 18 months is repeated rapid serological testing, which increases the risk of false HIV diagnoses and infant mortality if not treated in time [ 52 ]. The 2 (8%, 2/25) HIV-exposed children who were infected died before they could receive a confirmatory diagnosis and adequate ART.…”
Section: Discussionmentioning
confidence: 99%
“…This circumstance is of particular concern at HCM, which is in a higher-HIV prevalence province and has approximately 60% more admissions per month, but had fewer inpatient POC tests performed per month than did HCB (16.5 versus 18.3). 19 11,[20][21][22] Concerningly, a study of pediatric inpatient PITC from wards in Mozambique reported that coverage rates are low. 13 Routine opt-out rapid antibody testing of breastfeeding mothers is a crucial first step to newly identify HEIs who need EID testing, and this step can help improve POC EID platform utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to changing transmission dynamics and recent evidence that rapid serologic testing has a high rate of false negatives, the WHO now recommends that the 9-month rapid serologic test may be replaced with a virologic test. [4][5][6] There are a number of times when loss to follow-up (LTFU) occurs throughout the EID cascade, from the time the patient presents for sample collection to the caregiver's receipt of results and the clinical decision-making. Emerging evidence has shown that POC EID significantly reduces turnaround time (TAT), increases the percentage of results returned to caregivers, and increases the percentage of HIV-infected infants initiated on ART.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to changing transmission dynamics and recent evidence that rapid serologic testing has a high rate of false negatives, the WHO now recommends that the 9-month rapid serologic test may be replaced with a virologic test. 4 -6…”
Section: Introductionmentioning
confidence: 99%